2016
DOI: 10.1017/s1041610216001113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cognitive impairment on fall risk among elderly nursing home residents

Abstract: This study provides evidence indicating that fall risk factors do not hold a direct correlation with the level of cognitive impairment among elderly nursing home care residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 44 publications
4
10
0
2
Order By: Relevance
“…Only RF reported that the total number of residents was an important factor in falls, consistent with Thomas et al [42], but not with Van Doorn et al [7]. The RF and SVM radical reported that the proportion of residents with cognitive dysfunction related to falls, consistent with preceding research [6][7][8], but inconsistent with Datta et al [34].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Only RF reported that the total number of residents was an important factor in falls, consistent with Thomas et al [42], but not with Van Doorn et al [7]. The RF and SVM radical reported that the proportion of residents with cognitive dysfunction related to falls, consistent with preceding research [6][7][8], but inconsistent with Datta et al [34].…”
Section: Discussionsupporting
confidence: 57%
“…The proportion of residents prescribed psychiatric medications and urinary incontinence were top factors in the logistic regression, RF, SVM polynomial, SVM radial, and SVM sigmoid. Psychiatric medication was a very strong predictor of falls, consistent with previous research [6,7,9,10,[31][32][33], but inconsistent with a couple of studies [34,35]. The proportion of residents with urinary incontinence was an important factor in falls, supported in previous research [9][10][11][12], but not supported in other studies [7,32].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…En nuestro estudio, el deterioro cognitivo se asoció al riesgo de caídas según AF, pues encontramos que los adultos mayores con deterioro cognitivo tienen mayor probabilidad de riesgo de caídas, con una razón de prevalencias que triplica las probabilidades de tener un AF alterado, en un modelo ajustado por educación, número de comorbilidades, polifarmacia y edad. Este hallazgo está en línea con otros estudios como el de Seijo-Martínez et al, [23] y Gómez et al, [24] donde el estado cognitivo de los adultos mayores tuvo una asociación estadísticamente significativa con el riesgo de caídas, demostrando que a mayor severidad de deterioro cognitivo en el adulto mayor se incrementa la probabilidad del riesgo de caídas; de manera similar, Thanthrige et al, [25] y Azevedo et al, [26] evidenciaron también, la relación existente entre el desempeño cognitivo y el riesgo de caídas.…”
Section: Discussionunclassified
“…Análisis bivariado de prueba de alcance funcional y covariables del estudio (n=1786). De forma similar, también se encontró asociación entre el sexo femenino y a la polifarmacia como factores de riesgo para caídas, acorde a lo hallado por estudios previos [23,27] . Adicionalmente, el estudio de Azevedo et al, [26] evidenció que los adultos mayores del sexo femenino tenían mayor riesgo de presentar caídas y que este riesgo se incrementaba ante la presencia de comorbilidades.…”
Section: Tablaunclassified